2014
DOI: 10.1186/preaccept-1563099569137345
|View full text |Cite
|
Sign up to set email alerts
|

Onset of activity of fluralaner (BRAVECTO¿) against Ctenocephalides felis on dogs

Abstract: Single oral fluralaner administration rapidly eliminates existing flea infestations and provides excellent protection against fleas over 12 weeks following treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 8 publications
3
31
0
Order By: Relevance
“…Fluralaner (Bravecto®; Merck Animal Health) is the only isoxazoline that provides 12 weeks of immediate and persistent flea and tick efficacy for dogs [69]. Field studies in the USA, Europe and Australia demonstrated the safety and efficacy of orally administered fluralaner for reducing flea and tick infestations on dogs [1012].…”
Section: Introductionmentioning
confidence: 99%
“…Fluralaner (Bravecto®; Merck Animal Health) is the only isoxazoline that provides 12 weeks of immediate and persistent flea and tick efficacy for dogs [69]. Field studies in the USA, Europe and Australia demonstrated the safety and efficacy of orally administered fluralaner for reducing flea and tick infestations on dogs [1012].…”
Section: Introductionmentioning
confidence: 99%
“…In dogs experimentally infested with fleas, the fluralaner chewable tablet showed early onset of flea killing at 2 h and 100% flea killing at 12 h post-administration [1]. This high level of efficacy was sustained for 12 weeks, with 98.0% to 100% reductions in mean live flea counts at 8, 12, and 24 h after experimental reinfestations.…”
Section: Introductionmentioning
confidence: 99%
“…Fluralaner belongs to this new class and has prolonged activity against fleas and ticks after a single oral dose (Kilp et al, 2014) of 25 mg/kg, with no adverse effects observed during a safety trial, even at higher doses (Walther et al, 2014). No side effects were observed by the authors of previous studies either (Taenzler et al, 2014;Wengenmayer et al, 2014;Fourie et al, 2015). However, one study reported inappetence, vomiting, and diarrhea (Rohdich et al, 2014).…”
Section: Introductionmentioning
confidence: 99%